Positive Behavior Support in Secondary Schools : a Practical Guide. - Young, Ellie L. (Practical Intervention in the Schools., 2011)
This much-needed guide shows how to implement positive behavior support (PBS) strategies in secondary settings, using a three-tiered approach. The authors adapt the core ideas of PBS to the developmental context of adolescence and the organizational structures of middle schools and junior and senior high schools. With an emphasis on data-based decision making, the book provides ideas and examples for meeting the behavioral needs of all students, from those with emerging concerns to those with ongoing, chronic problems. It takes practitioners step by step through planning, implementing, evaluat.